1997
DOI: 10.1359/jbmr.1997.12.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Trabecular Bone Structure with Age, Bone Mineral Density, and Osteoporotic Status: In Vivo Studies in the Distal Radius Using High Resolution Magnetic Resonance Imaging

Abstract: High resolution magnetic resonance (MR) images of the distal radius were obtained at 1.5 Tesla in premenopausal normal, postmenopausal normal, and postmenopausal osteoporotic women. The image resolution was 156 microm in plane and 700 microm in the slice direction; the total imaging time was approximately 16 minutes. An intensity-based thresholding technique was used to segment the images into trabecular bone and marrow, respectively. Extensions of standard stereological techniques were used to derive measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
282
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 403 publications
(307 citation statements)
references
References 25 publications
21
282
2
2
Order By: Relevance
“…I M was taken as the intensity at the peak position plus half the peak width. Using the mean intensity of the trabecular region, I O , the threshold is set to give a fraction of bone pixels, f = N bone /N total , satisfying the equation fI B + (1-f)I M = I O [5]. The resulting binarized image for one slice is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I M was taken as the intensity at the peak position plus half the peak width. Using the mean intensity of the trabecular region, I O , the threshold is set to give a fraction of bone pixels, f = N bone /N total , satisfying the equation fI B + (1-f)I M = I O [5]. The resulting binarized image for one slice is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) provides unique capabilities for the study of the structural aspects of both trabecular and cortical bone, allowing in vivo, noninvasive, three-dimensional (3D) structure assessment without the use of ionizing radiation. Previous studies have demonstrated the usefulness of both high-resolution imaging (HR-MRI) [1][2][3][4][5][6] and MR relaxometry [7][8][9][10][11] for deriving structural parameters for the assessment of trabecular bone. For the current study we are concerned with HR-MRI, in which the trabecular structure is determined indirectly from a scan in which the bone marrow shows as a high intensity and the signal voids are assumed to be volumes of bone.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold depends significantly on the imaging modality and may vary depending on the operator. Based on a dual reference limit and assuming a biphasic model, as previously validated (20), a global threshold was calculated and the images were binarized into a bone phase and a marrow phase. The segmented binary image was used to compute (per slice and ROI) trabecular bone parameters, such as the apparent trabecular bone volume fraction (BV/TV), apparent trabecular number (Tb.N), apparent trabecular separation (Tb.Sp), and apparent trabecular thickness (Tb.Th) analogous to standard bone histomorphometry (25).…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of human trabecular bone structure using MRI techniques showed that it was possible to quantify the trabecular architecture and derive such measures as trabecular width, trabecular bone volume fraction, and mean intercept length, as well as quantitative measures of texture, such as the fractal characteristics of the trabecular bone network (19)(20)(21). Majumdar et al (20) derived structural parameters in premenopausal healthy women and in postmenopausal women with osteoporosis and correlated the data with peripheral quantitative CT bone mineral density (BMD) and spinal fracture status.…”
mentioning
confidence: 99%
See 1 more Smart Citation